2022
DOI: 10.1002/adfm.202111470
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Dirac Semimetal Vertical Heterostructures for Advanced Device Architectures

Abstract: Exploiting the extraordinary transport and optical properties of 3D topological semimetals for device applications requires epitaxial integration with semiconductors to carefully control carrier transport, yet no studies have established heteroepitaxy on top of any topological semimetals to date. Here, a novel approach toward fabricating heterostructures is demonstrated by epitaxially incorporating the Dirac semimetal Cd 3 As 2 between Zn x Cd 1-x Te and CdTe layers via molecular beam epitaxy on GaAs (001) sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Parts of the top layers are etched up to the GaSb substrate, and gold electrodes are deposited on Cd 3 As 2 and GaSb by magnetron sputtering. Since the bandgap of Zn x Cd 1– x Te alloy is much larger than those of Cd 3 As 2 and GaSb, the epitaxial heterostructure is a dual-Schottky junction. , As shown in Figure b, the band diagram with zero bias reveals the principle of the broadband photoresponse, where the electron affinity of three layers and the bandgaps of Zn x Cd 1– x Te and GaSb are marked. Schottky junctions are formed between Cd 3 As 2 /Zn x Cd 1– x Te and Zn x Cd 1– x Te/GaSb interfaces, and the barrier heights are E 1 and E 2 , respectively. To further analyze the principles and confirm the barrier heights, 2-probe temperature-dependent biased dark current ( I – V ) measurements of our heterostructure thin films were carried out (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…Parts of the top layers are etched up to the GaSb substrate, and gold electrodes are deposited on Cd 3 As 2 and GaSb by magnetron sputtering. Since the bandgap of Zn x Cd 1– x Te alloy is much larger than those of Cd 3 As 2 and GaSb, the epitaxial heterostructure is a dual-Schottky junction. , As shown in Figure b, the band diagram with zero bias reveals the principle of the broadband photoresponse, where the electron affinity of three layers and the bandgaps of Zn x Cd 1– x Te and GaSb are marked. Schottky junctions are formed between Cd 3 As 2 /Zn x Cd 1– x Te and Zn x Cd 1– x Te/GaSb interfaces, and the barrier heights are E 1 and E 2 , respectively. To further analyze the principles and confirm the barrier heights, 2-probe temperature-dependent biased dark current ( I – V ) measurements of our heterostructure thin films were carried out (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…The current density has been reported to exceed 5 A/mm for a carrier density of 5 × 10 12 cm –2 , corresponding to an exceptionally high drift velocity of u = 6.3 × 10 5 m s –1 ≈ 0.6 v F . Epitaxially grown thin films of Cd 3 As 2 have also demonstrated high mobility and v F . …”
Section: Resultsmentioning
confidence: 99%
“…The enlarged high-resolution TEM image further showed an atomically sharp interface between (Cd 1−x Zn x ) 3 As 2 and Sb 2 Se 3 . The thermally deposited Sb 2 Se 3 film exhibited polycrystalline characteristics with chaotic lattice fringes, while the epitaxial (Cd 1−x Zn x ) 3 As 2 was monocrystalline, with distinct lattice fringes [28,36]. The photoelectrical properties of the (Cd 1−x Zn x ) 3 As 2 /Sb 2 Se 3 double-heterojunction lineararray PD were investigated at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, its extremely attractive optical and electronic characteristics, including remarkable charge transport, unique topological zero energy-band architecture, strong lightmatter interaction, and high chemical stability, make it promising for mid/far infrared photodetection [21][22][23]. However, research has revealed that 3D Dirac semimetal PDs, owing to device geometry (such as photoconductive or photovoltaic), always suffer from high device noise and surface leakage current caused by a relatively high carrier density and charge mobility, which deteriorate their photodetection performance in terms of detectivity and response speed [24][25][26][27][28][29]. Fortunately, the moderate chemical doping of zinc (Zn) into a Cd 3 As 2 film can effectively compensate for the residual electron concentration to reduce the electron state density via the formation of the 3D Dirac semimetal (Cd 1−x Zn x ) 3 As 2 , as revealed in previous studies [30][31][32].…”
Section: Introductionmentioning
confidence: 99%